Synthesis of Cyclophenacene‐ and Chiral‐Type Cyclophenylene‐Naphthylene Belts - Nogami, Juntaro; Nagashima, Yuki; Sugiyama, Haruki; Miyamoto, Kazunori; Tanaka, Yusuke; Uekusa, Hidehiro; Muranaka, Atsuya; Uchiyama, Masanobu; Tanaka, Ken (Angewandte Chemie International Edition, 2022)
We report the synthesis of a [20]cyclophenacene‐type cyclophenylene‐naphthylene (CPN) belt and the enantioselective synthesis of chiral‐type CPN belts (up to >99 % ee) by the cationic rhodium(I)‐catalyzed intramolecular [2+2+2] cycloaddition of naphthalene‐embedded cyclic polyynes. The synthesis of a depth‐expanded CPN belt was also attempted, but the final intramolecular [2+2+2] cycloaddition was unsuccessful. Theoretical calculations clarified that the reactivity depends on the stability of the transition state in the initial oxidative cycloaddition step which is subject to molecular strain. The cylindrical structures of these CPN belts were confirmed by X‐ray crystallographic analyses. As a result of π‐extension through the introduction of naphthalenes in the chiral‐type CPN belts, the anisotropy dissymmetry factors of electronic circular dichroism and circularly polarized luminescence are amplified compared with the corresponding zigzag‐type chiral cyclophenylene belts. The synthesis of a [20]cyclophenacene‐type cyclophenylene‐naphthylene (CPN) belt and the enantioselective synthesis of chiral‐type CPN belts have been achieved by the cationic rhodium(I)‐catalyzed intramolecular [2+2+2] cycloaddition of naphthalene‐embedded cyclic polyynes. However, the synthesis of a depth‐expanded CPN belt was unsuccessful. Theoretical calculations clarified that the reactivity depends on the stability of the transition state which is subject to ring strain.